Making Strategies of Agency and Economic Empowerment Visible: The Case of Pakistani Women in Barcelona - Güell Torrent, Berta; Arrasate Hierro-Olavarría, Marina; Solé Arraràs, Ariadna (Migraciones. Publicación del Instituto Universitario de Estudios sobre Migraciones, 2020)
Migrant Muslim women are confronted with a stereotyped image of housewives and passive subjects in their processes of incorporation into the host society, that assumes their invisibility in the labour market as intrinsic and “natural”. This article pretends to question this image and shed light on the agency processes of Pakistani women in Barcelona in the field of productive and reproductive economy. In particular, it seeks to examine the structural and cultural obstacles that these women face when accessing the labour market, as well as the agency and empowerment strategies they deploy to overcome them. Based on two recent studies focused on this group, the results show that agency is embedded (Khurshid, 2015) in the structural constraints of the host society, as well as in the system of values and patriarchal gender ideologies of the Pakistani community.
Keywords: gender; agency; empowerment; Pakistani migration